2022
DOI: 10.3390/ijms23084203
|View full text |Cite
|
Sign up to set email alerts
|

Role of Drosophila in Human Disease Research 2.0

Abstract: The fruit fly Drosophila melanogaster is a highly tractable animal model to study various human diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Drosophila is easy to maintain and manipulate in the laboratory. Drosophila has a relatively short generation time, and production of a large number of offspring guarantees statistical significance of the obtained experimental data (Table 2) [104][105][106]. Mutants, overexpression and RNAi lines for many of the Drosophila replicative DNA polymerase genes are available from various stock centres.…”
Section: Possible Application Of Drosophila Models To Study Human Dis...mentioning
confidence: 93%
See 1 more Smart Citation
“…Drosophila is easy to maintain and manipulate in the laboratory. Drosophila has a relatively short generation time, and production of a large number of offspring guarantees statistical significance of the obtained experimental data (Table 2) [104][105][106]. Mutants, overexpression and RNAi lines for many of the Drosophila replicative DNA polymerase genes are available from various stock centres.…”
Section: Possible Application Of Drosophila Models To Study Human Dis...mentioning
confidence: 93%
“…In Drosophila, cancer models have been established and used to study various aspects of cancer research [107]. Drosophila tumour suppressor lgl cooperates with scribble and discs sufficiently large to maintain apicobasal polarity of epithelial cells [106]. Their mutations induce disorganization of epithelial tissue architecture followed by formation of multi-layered metastatic tumours.…”
Section: Possible Application Of Drosophila Models To Study Human Dis...mentioning
confidence: 99%
“…It has been suggested that the minimum number of animals in a study is 3, but the maximum should be 6 or 7 [64]. In the future, the development of in vitro models mimicking humane physiological systems or in vivo model with less ethical concerns (such as drosophila) could assist Original Research this study [65]. Moreover, our extensive knowledge could make direct intervention human subjects possible.…”
Section: Future Directionmentioning
confidence: 99%
“…The advent of wearable devices or recent advances in a comprehensive monitoring platforms have made longitudinal studies using human and mammalian models much easier. However, invertebrate models such as the fruit fly ( Drosophila melanogaster ) continue to be useful as models for understanding human diseases and aging due to their short lifespan, the availability of powerful genetic manipulation tools, and the conservation of biological processes and signaling pathways between mammals [ 111 , 112 ]. Although fruit flies show cellular senescence phenotypes [ 113 , 114 , 115 ], flies are not the best model for studying cellular senescence in the context of aging, as most cells in adult flies are postmitotic.…”
Section: Dnb Analysis In Metabolismmentioning
confidence: 99%